A Limit Theorem for Twists of L-Functions of Elliptic Curves - Garbaliauskienė, Virginija; Laurinčikas, Antanas (Mathematical Modelling and Analysis, 2014)
In the paper, a limit theorem for weakly convergent probability measures on the complex plane for twisted with Dirichlet character L-functions of elliptic curves with an increasing modulus of the character is proved.